Website Quality in Asia: Testing a Measurement Instrument in a Chinese Context - Morales, Miguel; Peng, Lei (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2021)
In this study we investigate the psychometric properties of a Chinese version of a perceived website quality (PWQ) measurement instrument. The results of our study confirmed the four-factor structure of the scale scores and that the scale has good internal consistency. CFA results support the convergent and discriminant validity of the scales scores for the first factor measurement model. Our findings also showed that a single higher-order factor accounts for the variance among the four lower-order factors. In view of its sound psychometric properties, the Chinese version of the PWQ scale is a useful instrument to evaluate website quality in a Chinese context.